Integrating Design for Manufacturing and Assembly Principles in Modular Home Construction: A Comprehensive Framework for Enhanced Efficiency and Sustainability - Sadaf Montazeri; Nicole Odo; Syed Abdul Wasey Naqvi; Zhen Lei (Buildings)
The growing demand for sustainable and efficient construction practices has led to an increased interest in modular construction, with design for manufacture and assembly emerging as a pivotal approach. Despite its potential, the integration of design for manufacture and assembly in modular home construction lacks a structured methodology, posing challenges in aligning design, manufacturing, and assembly processes. This paper introduced a framework aimed at systematically incorporating design for manufacturing and assembly principles into modular home production, leveraging different software tools in the design stage for modular design standardization and streamlined manufacturing and assembly processes. Following a mixed-method research methodology, a comprehensive literature review was conducted to identify research gaps. To address these gaps, a framework was developed focusing on design, manufacturing, and assembly considerations, and retrospective validation of the framework was conducted to confirm its effectiveness. This study revealed the significant benefits of integrating design for manufacturing and assembly principles utilizing advanced digital tools, through a hybrid approach using 2D drafting software and 3D BIM software. The findings indicated that implementing design for manufacturing and assembly principles led to a 40% reduction in design phase duration and a 48% decrease in production errors. This paper offers a structured guide for practitioners while providing a basis for further research in sustainable modular construction.